The Plate Objective Scoring Tool (POST): Further Reflections and Extended Applications - Abbas TO (Dove Medical Press, 2021)
Tariq O Abbas1– 4 1Pediatric Urology Section, Sidra Medicine, Doha, Qatar; 2College of Medicine, Qatar University, Doha, Qatar; 3Weill Cornell Medicine Qatar, Doha, Qatar; 4Regenerative Medicine Research Group, Department of Health Science and Technology, Aalborg University, Aalborg, DenmarkCorrespondence: Tariq O Abbas Email tabbas@sidra.org; tariq2c@hotmail.comAbstract: Hypospadias is a common birth defect of the male external genitalia. However, there are conflicting arguments about the optimal classification approach and ideal surgical technique. We have introduced the Plate Objective Scoring Tool (POST) to define critical glanular phenotypic landmarks of the urethral plate. We propose that POST can objectively, reproducibly, and accurately determine urethral plate quality, thus permitting robust comparison between the different surgical techniques commonly utilized in hypospadias repair. Furthermore, the POST scoring system represents a versatile tool that can objectively quantify key variables in hypospadiology that are currently not well defined. Further validation of POST should lead to better identification and management of postoperative complications.Keywords: hypospadias, scoring tool, classification, POST, objective